Evaluation of nonlinear optical properties of neutron irradiated polymethyl methacrylate and their recovery over time - A.M. Beigzadeh; M.R. Rashidian Vaziri; B. Shakeri Jooybari (Results in Optics)
Poly(methyl methacrylate) (PMMA) is a synthetic polymer that is widely used in the world due to its transparency, toughness, ease of shaping, low cost, and high resistance to UV light and weathering. It has many applications in various industries such as nuclear and space industries in the form of optical PMMA fibers and may be subjected to high energy neutrons. The structural and optical properties of PMMA change due to neutron irradiation, which may have adverse effects on its functionality in these applications. In this study, the effect of reactor neutron irradiation on structural and nonlinear optical properties of PMMA has been experimentally investigated. It is shown that neutron irradiation results in inducing a negative nonlinear refractive index in PMMA that gradually decreases over time. It is further shown that the induced nonlinear refractive index decreases to 0.4 of its initial value after 80 days. It is proposed that this negative nonlinear refractive index can be an additional source of radiation induced attenuation (RIA) in PMMA optical fibers. To the best of our knowledge, this is the first indication that negative nonlinearity can be a source of RIA in PMMA fibers. Aside from its adverse effects on signal propagation in PMMA fibers, the induced negative nonlinearity by neutrons can be beneficially used to design new photonic components such as all-optical switches, modulators, and more with bulk PMMA pieces.